A decoy receptor 3 analogue reduces localised defects in phagocyte function in pneumococcal pneumonia. Issue 11 (26th June 2012) - Marriott, Helen M; Daigneault, Marc; Thompson, Alfred A R; Walmsley, Sarah R; Gill, Sharonjit K; Witcher, Derrick R; Wroblewski, Victor J; Hellewell, Paul G; Whyte, Moira K B; Dockrell, David H
Abstract : Background: Therapeutic strategies to modulate the host response to bacterial pneumonia are needed to improve outcomes during community-acquired pneumonia. This study used mice with impaired Fas signalling to examine susceptibility to pneumococcal pneumonia and decoy receptor 3 analogue (DcR3-a) to correct factors associated with increased susceptibility. Methods: Wild-type mice and those with varying degrees of impairment of Fas ( lpr ) or Fas ligand signalling ( gld ) were challenged with Streptococcus pneumoniae and microbiological and immunological outcomes measured in the presence or absence of DcR3-a. Results: During established pneumonia, neutrophils became the predominant cell in the airway and gld mice were less able to clear bacteria from the lungs, demonstrating localised impairment of pulmonary neutrophil function in comparison to lpr or wild-type mice. T-cells from gld mice had enhanced activation and reduced apoptosis in comparison to wild-type and lpr mice during established pneumonia. Treatment with DcR3-a reduced T-cell activation and corrected the defect in pulmonary bacterial clearance in gld mice. Conclusions: The results suggest that imbalance in tumour necrosis factor superfamily signalling and excessive T-cell activation can impair bacterial clearance in the lung but that DcR3-a treatment can reduce T-cell activation, restore optimal pulmonary neutrophil function and enhance bacterial clearance during S pneumoniae infection.